Perusahaan Pembuat Spare Part Motor Mantri Karbu: Mengoptimalkan Proses Produksi dengan Metode Transformasi - Kharis Nuril Huda; Rehan Alldy Kusuma; Faruq Abdul Ghani; Ryan Dipta Bagaswara Labda Jaya; Titis Purwaningrum (Jurnal Manuhara : Pusat Penelitian Ilmu Manajemen dan Bisnis, 2025)
This article discusses efforts to optimize the production process at the motorcycle carburetor company "Mantri Karbu" through the application of transformation methods. In the automotive industry, production efficiency is key to enhancing competitiveness and meeting the ever-growing market demand. This study identifies various challenges faced by Mantri Karbu, including long production times, resource waste, and inconsistent product quality. By implementing transformation methods, which include workflow analysis, waste reduction, and employee skill enhancement, the company can improve productivity and operational efficiency. The results of this implementation show a significant increase in production cycle time, a reduction in operational costs, and an improvement in customer satisfaction. This article aims to provide insights for other companies in similar industries to adopt effective strategies for optimizing their production processes.